2018
DOI: 10.1002/aic.16070
|View full text |Cite
|
Sign up to set email alerts
|

CO2 capture by methanol, ionic liquid, and their binary mixtures: Experiments, modeling, and process simulation

Abstract: The CO 2 solubility data in the ionic liquid (IL) 1-allyl-3-methylimidazolium bis(trifluoromethyl sulfonyl)imide, methanol (MeOH), and their mixture with different combinations at temperatures of 313.2, 333.2, and 353.2 K and pressures up to 6.50 MPa were measured experimentally. New group binary interaction parameters of the predictive universal quasichemical functional-group activity coefficient (UNIFAC)-Lei model, which has been continually advanced by our group, were introduced by correlating the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 114 publications
0
34
0
Order By: Relevance
“…Lei et al 2 extended the original UNIFAC model proposed by Fredenslund et al 3 from conventional solvents to IL systems to further build the current UNIFAC models for ILs with the most complete parameters consisting of 75 main groups and 130 subgroups covering a wide pressure (0.01-500.0 bar) and temperature (243-453 K) range. [4][5][6] The UNIFAC model has been widely employed by researchers as valuable tools for predicting the activity coefficients of mixed systems with ILs or conventional solvents. 7,8 At present, The UNIFAC model has become one of the most widely applied thermodynamic models for quantitatively predicting thermodynamic properties, such as GLE, VLE, and LLE of the systems containing ILs.…”
Section: Original Unifac Modelmentioning
confidence: 99%
“…Lei et al 2 extended the original UNIFAC model proposed by Fredenslund et al 3 from conventional solvents to IL systems to further build the current UNIFAC models for ILs with the most complete parameters consisting of 75 main groups and 130 subgroups covering a wide pressure (0.01-500.0 bar) and temperature (243-453 K) range. [4][5][6] The UNIFAC model has been widely employed by researchers as valuable tools for predicting the activity coefficients of mixed systems with ILs or conventional solvents. 7,8 At present, The UNIFAC model has become one of the most widely applied thermodynamic models for quantitatively predicting thermodynamic properties, such as GLE, VLE, and LLE of the systems containing ILs.…”
Section: Original Unifac Modelmentioning
confidence: 99%
“…Process modeling, simulation, and optimization are crucial to design an industrial tail gas purification process. The process simulation can provide data support for the industrial application of the technology by analyzing the parameters of the system and discover the technical bottleneck in advance. For example, Shiflett et al simulated a CO 2 capture process using pure [C 4 Mim]­[Ac], and the results suggested that 16% energy consumption could be saved compared with traditional processes. Liu et al studied shale gas CO 2 decarbonation process using [C 4 Mim]­[NTf 2 ], and the result indicated that the IL-based process can reduce over 42.8% of energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that some ILs have very distinct solvation capacities for different gases, indicating the high potential of using ILs as solvents in gas separations . Meanwhile, work regarding the utilization of ILs as solvents in gas separation tasks from CO 2 capture to shale gas purification has been widely studied. , …”
Section: Introductionmentioning
confidence: 99%